Needs of forensic psychiatric patients with schizophrenia in five European countries - Oberndorfer, Raimund; Alexandrowicz, R. W.; Unger, A.; Koch, M.; Markiewicz, I.; Gosek, P.; Heitzman, J.; Iozzino, L.; Ferrari, C.; Salize, Hans Joachim; Picchioni, M.; Fangerau, Heiner; et al. (Social psychiatry and psychiatric epidemiology, 2023)
The purpose was to compare the frequency of needs of patients with schizophrenia in forensic services across five European countries as assessed by both the patients and their care staff.